Interpretation of Hormone Levels in Older Patients: Points for Consideration - Krystyna Sztefko; Patrycja Szybowska (International Journal of Endocrinology)
Blood hormone and tumor marker concentrations are usually determined by immunochemical methods which are based on an unique reaction between antigen and assay capture antibody. Despite the speed and simplicity of assays performance on automatic immunochemistry platforms, the interpretation of final results requires a deep knowledge of method fallibility. General lack of immunoassays standardization, presence of cross-reacting substances in patient’s sample, limitation of free hormones measurement due to abnormal analyte binding protein concentrations, assay interferences due to patient’s autoantibodies, and heterophilic antibodies, as well as proper interpretation of very low- and very high-sample analyte levels, are the main points discussed in respect to hormones and tumor markers measurement in geriatric population.